Enantioselective Synthesis of the Tricyclic Core of FR901483 Featuring a Rhodium-Catalyzed [2+2+2] Cycloaddition - Perreault, Stéphane; Rovis, Tomislav (Synthesis, 2013)
An efficient approach to the tricyclic framework of FR901483 is described. The sequence features a [3,3]-sigmatropic rearrangement of a cyanate to an isocyanate, followed by its subsequent asymmetric rhodium-catalyzed [2+2+2] cycloaddition with a terminal alkyne for the synthesis of the indolizidine core. The aza-tricyclic core is completed using an intramolecular benzoin reaction to close the last ring of the natural product. Through a model study of the key cycloaddition, we evaluated the impact of different substituents on the tether of the alkenyl isocyanate.
Keywords: [3,3]-sigmatropic rearrangement; isocyanate; [2+2+2] cycloaddition; indolizidine; FR901483